2008
DOI: 10.1021/cm703499q
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molecular Packing on Field-Effect Performance of Single Crystals of Thienyl-Substituted Pyrenes

Abstract: A series of pyrene derivatives containing thienyl groups, 1−3, has been prepared using the Suzuki coupling reaction. Recrystallization from solution and physical vapor transport (PVT) method afforded different types of crystals of 1. From the mixture of isomers of 2, the 1,8-isomer preferably crystallized from solution, whereas the 1,6-isomer crystal was obtained by the PVT method. Fabricating single-crystal-based field-effect transistors of the above compounds we directly compared the field-effect performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…This leads to a relatively low band gap for the tetra-substituted derivative PP4. When compared with the known thienylpyrenes, 24,38 the oxidation potentials of the new compounds are less positive attributable to the electron-richness arising from the phenothiazine end-capping. …”
Section: Electrochemical Propertiesmentioning
confidence: 87%
See 1 more Smart Citation
“…This leads to a relatively low band gap for the tetra-substituted derivative PP4. When compared with the known thienylpyrenes, 24,38 the oxidation potentials of the new compounds are less positive attributable to the electron-richness arising from the phenothiazine end-capping. …”
Section: Electrochemical Propertiesmentioning
confidence: 87%
“…Recently, Ashizawa et al explored a series of thienylpyrenes for OFET application and found them to exhibit excellent p-type performance. 24 Kimura et al investigated the utility of X-shaped poly-thienyl pyrenes in bulk heterojunction solar cells (BHJs) and found to exhibit decent device parameters. 25 Among the heterocyclic chromophores, phenothiazine is one of the prototypical molecules and its unique butterfly configuration and high electron rich character are beneficial for its potential function in optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…By introducing end-capped octyl groups and treatmento f the dielectric surface, thiophene-containing compound 1 exhibited higherm obility than 1,8-bis(2-thienyl)pyrene [18] and pyrene derivatives that were substituted at the 2,7- [15] and 1,3,6,8-positions. Based on DFT calculations, bithiophene-containing compound 2 was found to contain large amounts of steric hindrance.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Pyrene-thiophene derivatives have been widely used in OFETs. [18] Ta king into account two favorable factors, that is, that terminal alkyl chains can act as ad riving force for molecular ordering in the solid state [19] and the length of conjugateds tructure, [20] we designed and synthesized two 1,8-substituted pyrene derivatives that were composed of ap yrene core, thiophene units, and end-cappedo ctyl chains. [18] Ta king into account two favorable factors, that is, that terminal alkyl chains can act as ad riving force for molecular ordering in the solid state [19] and the length of conjugateds tructure, [20] we designed and synthesized two 1,8-substituted pyrene derivatives that were composed of ap yrene core, thiophene units, and end-cappedo ctyl chains.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, high mobilities of 1.2 cm 2 V −1 s −1 for holes and 3 cm 2 V −1 s −1 for electrons were obtained by judging from the transient photocurrent of the pyrene crystal and calculating from the overlap integrals between two molecules at room temperature [89]. Because of the nonplanar structure, the tetrasubstituted-derivatives using pyrene as core including 33 and 34 tend to afford low mobilities [90][91][92]. However, the derivatives 35 and 36 using pyrene as an end-capped group and linear pyrene derivative 37 showed high mobilities [93][94][95].…”
Section: Pyrene and Derivativesmentioning
confidence: 99%